Kart og krim: Litterære kart og steders betydning i krimserier for barn - Goga, Nina (Tidskrift för litteraturvetenskap, 2014)
Maps and Crime. Literary Maps and the Meaning of Places in Crime Series for Children In literature, and especially in crime fiction, the site of the action and the crime itself are often as crucial an element for the story as the main characters. Most theoretical approaches to crime literature have been primarily concerned with discussing genre typologies on the basis of the plot, the investigator and the investigation. Less attention has been paid to the landscape of crime fiction in both theory and analysis. In this article, I will discuss two series: Bjørn Sortland’s Art Detective Series and Martin Widmark and Helena Willis’ Whodunit Detective Agency Series. These very popular series have been chosen as examples because all the books in the series provide the readers with a map of the location of the action. In addition, both series are classified as chapter and young reader books. This means that the maps may provide strategic reading support for young and often inexperienced readers. Maps are not an uncommon peritextual phenomenon in books for children, and the maps in the series discussed here are therefore initially considered in the context of other maps in children’s literature. The article goes on to discuss how the maps and the places function as important tension-reinforcing elements in crime novels, and also as an expression of the mystery genre and the society the series represents.